The Effect of Yoga Therapy on Premenstrual Syndrome in Adolescent Girls at SMP Swasta Muhammadiyah 1 Medan - Laili, Alfi; Desi Handayani Lubis; Safitri, Yulia (International Journal of Public Health Excellence (IJPHE), 2024)
A teenage daughter often suffers from painful menstrual moments (premenstruation syndrome). The prevalence of premenstruation syndrome in Central Java is 56%. Although painful, it is not dangerous; however, it can bother activity daily. Possible non-pharmacological therapy used to overcome premenstrual syndrome is yoga practice. A study introduction found that 24 out of 30 female students suffer painful periods. Research purposes This is to know the influence of yoga practice on the level of painful menstruation in students of Muhammadiyah 1 Medan Private Middle School. Types of research This is a quantitative study with a pseudo-design experiment. Consecutive sampling was used to collect data from 20 respondents with the use of a painful numeric scale. As for the analysis using the Wilcoxon test, the scoring scale for painful numeric before and after yoga practice shows a scale of 5.15 and 3.00. A bivariate test shows the p-value is 0.000. There is an influence of yoga practice on the level of painful menstruation in students of Muhammadiyah 1 Medan Private Middle School.